Bacterial rather than fungal diversity and community assembly drive soil multifunctionality in a subtropical forest ecosystem. Issue 1 (27th December 2021) - Han, Shun; Tan, Shuang; Wang, Achen; Chen, Wenli; Huang, Qiaoyun
Summary: Microbial diversities are key drivers of soil multifunctionality in terrestrial ecosystems and are important for stability and productivity of ecosystems. However, the relationships among microbial diversity, community assembly and soil multifunctionality in forest ecosystems remained unclear. Here, soil samples were collected from a subtropical forest ecosystem, Lushan Mountain, China. High‐throughput sequencing was employed to reveal the bacterial/fungal community assembly and biodiversity, as well as 10 enzyme activities were measured to assess soil multifunctionality. We found that soil multifunctionality was negatively regulated by bacterial and fungal alpha diversity, implying a higher potential functional redundancy in this forest soil. The null model indicated that deterministic processes (variable selection) and stochastic processes (dispersal limitation) govern bacterial and fungal phylogenetic turnover, respectively. Correlation analysis revealed that bacterial rather than fungal community assembly processes have a significant linkage to soil multifunctionality. These observations projected that soil variables could regulate multifunctionality by shaping the phylogenetic and taxonomic turnover of bacteria rather than fungi. In summary, our study highlighted that soil multifunctionality is mainly driven by bacterial diversity and community assembly processes while not fungal, presenting different views and knowledge of microbial diversity and community assembly processes in ecosystem functioning.